PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP PROFITABILITAS DENGAN PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN SEBAGAI VARIABEL MEDIATING PADA PERUSAHAAN MANUFAKTUR - RIE RIENITA PAALLO; ARDIANTO ARDIANTO (Jurnal Ekonomi dan Bisnis Airlangga, 2020)
Introduction: This study examines the effect of good corporate governance on the profitability, either directly or through CSR as an mediating variable in manufacturing companies listed in Indonesia Stock Exchange in the period of 2008-2012.Methods: Sampling method used is purposive sampling by using a balanced panel of data to obtain a sample of 135 companies. Good corporate governance as independent variables were measured usingfour internal mechanism that institutional ownership, managerialownership, board of directors, and audit committees.he research hypotheses were tested using path analysis model.Results: This study found that only institutional ownership had direct and significant impact on profitability. CSR disclosure only proven to be an mediating variable in the relationship between managerial ownership on the profitability of the company. Conclusion and suggestion: Companies should pay attention in the form of social responsibility to the environment and society.